The crisis caravan what's wrong with humanitarian aid? - Polman, Linda (Metropolitan Books, 2010)
Linda Polman takes us to war zones around the globe to show the often compromised results of aid workers' best intentions. It is time, Polman argues, to impose ethical boundaries, to question whether doing something is always better than doing nothing, and to hold humanitarians responsible for the consequences of their deeds. --from publisher description